Anisakis Larvae in Atlantic Wild Fish: Food Safety Hazards Driven by Trendy Diets - Rafael C. Duarte; Paula Ramos; Maria J. Santos; Rita Barracosa; Mónica Caldeira; Inês Magalhães; Ricardo Calado (Fish and Fisheries, 2026)
Zoonotic parasites are an increasingly recognised challenge for seafood safety. Anisakid nematodes currently represent the most significant fish‐borne parasitic threat in Atlantic wild fisheries. Recent regional surveys and global syntheses suggest significant increases in the prevalence and intensity of anisakid infections across multiple commercially important fish species, raising concerns for public health, marketability and consumer confidence. At the same time, the growing popularity of raw and lightly processed seafood has increased human exposure to anisakids, potentially amplifying infection risk independently of ecological changes in parasite abundance. Here, we synthesise current knowledge on anisakid parasitism in Atlantic fish and critically examine the interacting mechanisms that may be driving these trends. We highlight the roles of climate‐driven ecosystem change, recovery and redistribution of marine mammal definitive hosts, shifts in fish host ecology, evolving fishing and post‐capture handling practices, changing seafood consumption patterns, and major advances in parasite detection and diagnostics. While improved surveillance has undoubtedly increased reporting, converging evidence suggests that changes in host–parasite dynamics are also occurring. We further discuss practical mitigation options across the seafood value chain, from onboard handling and processing to retail, food service and consumer awareness, emphasising the need for coordinated, risk‐based approaches. Collectively, these developments challenge the long‐standing perception of wild fish, especially when consumed raw or lightly processed, as inherently safe, underscoring the importance of integrating ecological insight, consumer behaviour, technological innovation and public‐health guidance to ensure sustainable fisheries and safe seafood consumption.

Pulmonary fibrosis in horses associated with spontaneous Crotalaria juncea intoxication - Andrezza C. Andrade; Silvio M.C. Fonseca; Givaldo B. Silva Filho; Elizandra T. Melo; José R.P. Santos; Maria Luiza S.L. Frota; Jean M.B.S. Duarte; Joaquim Evêncio-Neto; Luiz B. Brito; Telma S. Lima; Nathalia S. Wicpolt; Franklin Riet-Correa; et al. (Toxicon, 2026)

Ohmic heating-assisted extraction of ginger bioactives: Synergistic impacts on extract composition and on the quality of high-protein milk beverages - Gabrielle P. Vieira; Carolina P.C. Martins; Thaís Regina C. Pereira; Lévison C. Cipriano; Maria B. Goulart; Jonas T. Guimarães; Mônica M. Pagani; Maria Carmela K.H. Duarte; Adriano G. Cruz; Sérgio B. Mano; Eliane T. Mársico; Erick A. Esmerino (Food Research International, 2026)

High meiofaunal diversity in the Azores revealed through DNA metabarcoding - Francesca Leasi; Nuno V. Álvaro; Luiz F. Andrade; Thiago Q. Araújo; Víctor Aramayo; Tom Artois; Will M. Ballentine; Franziska S. Bergmeier; Andrea Z. Botelho; Ariane Buckenmeyer; Ana T. Capucho; Irina Cherneva; et al. (Marine Biodiversity, 2026)
To advance understanding of meiofauna, key components of marine benthic ecosystems, an international team conducted a morphology-based taxonomic survey and workshop around São Miguel, the largest Azorean island, in 2019. The survey yielded critical baseline data on meiofaunal diversity and, despite taxonomic challenges that limited identification of certain taxa, laid a solid foundation for further research. To expand these findings, additional samples were analyzed using DNA metabarcoding, a powerful tool that assesses multiple facets of biodiversity, including richness, community composition, and phylogenetic diversity. Metabarcoding identified 480 meiofaunal amplicon sequence variants across 14 phyla, more than doubling the 180 taxa recorded through morphology alone. Of these, 298 (approximately 62%) belonged to phyla targeted during the morphology-based workshop. A comparison between the two approaches, focusing on clades addressed during the workshop, revealed overlapping but expanded patterns of diversity relative to morphology-based taxonomy. This consistency supports the metabarcoding’s ability to uncover meiofaunal diversity and underscores the importance of integrating both methods to achieve a more comprehensive understanding of biodiversity and ecological patterns. As the first metabarcoding study in the Azores, this work establishes a biodiversity baseline for a remote and understudied region, indicating greater benthic diversity than previously recognized. By revealing the complexity of these understudied ecosystems, this research contributes to document and support conservation of biodiversity in the Azores and emphasizes the need for further exploration of meiofaunal communities in isolated oceanic environments.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Out of sight, but not out of mind: Key issues regarding seafloor macrolitter monitoring - Georg Hanke; Miquel Canals; Ryota Nakajima; Melanie Bergmann; Francois Galgani; Daoji Li; George Papatheodorou; Christopher Kim Pham; Diva J. Amon; Michela Angiolillo; Lene Buhl-Mortensen; Alessandro Cau; et al. (Marine Pollution Bulletin, 2025)

Ohmic heating for attenuation of Lactobacillus acidophilus LA-5 in Minas Frescal cheese: probiotic survival, biological activity, and in vitro antimicrobial activity - Cássia P. Barros; Tatiana C. Pimentel; Ramon Silva; Maria Carmela K.H. Duarte; Eliane T. Mársico; Erick A. Esmerino; Pedro Henrique C. Felix; Carlos Augusto F. Oliveira; Beatriz L. Valente; Marcelo Cristianini; Mônica Q. Freitas; Adriano G. Cruz (Food Research International, 2025)

Sex Drives Intraspecific Scaling of Home Range Size in Mammals - Aline Giroux; Denis Valle; Eliezer Gurarie; Marcus Vinicius Vieira; James D. Forester; Luca Börger; Raissa Sepulvida; Nicole Barbour; Erika G. da Rocha; Julia Oshima; Fernanda C. de Azevedo; Frederico G. Lemos; et al. (Ecology Letters, 2025)
Understanding variation in home range size (HR) provides important insights into the underlying ecological processes driving space use. However, it remains unclear whether the interspecific allometric scaling of mammals' HR can also be consistently observed within species and for both sexes. To address this knowledge gap, we GPS‐tracked 349 resident individuals across Brazil, encompassing 18 mammal species. We estimated individuals' HR and modelled intraspecific variation in HR against body mass (BM) and sex. While males showed a positive allometric scaling similar to interspecific findings reported in the literature (exponent = 1.23), females' BM had no statistically discernible relationship with HR. We suggest that males have greater energetic and evolutionary incentives to expand their HR with increasing BM, and more physical capacity to do so. Traditional studies on HR scaling that disregard individual sex may, in reality, reflect an average of two distinct patterns, while failing to accurately represent either one.

Influence of UV-C radiation on the treatment of Minas Frescal cheese inoculated with Escherichia coli and Staphylococcus aureus - Laura R.C. Oliveira; Gabriel C. Bevilaqua; Neila M.S.C. Barbosa; Luciana Cristina L.A. Santana; Maria Terezinha S.L. Neta; Gustavo L.P.A. Ramos; Adriano G. Cruz; Maria Carmela K.H. Duarte (International Dairy Journal, 2025)

Infection by colombian datura virus induces leaf deformation associated with Indigenous selection of angel’s trumpet (Brugmansia spp.) - Sergio A. Hernández-Duarte; Oscar A. Oliveros-Garay; Adriana González; Maria C. Delgado-Niño; Federico Roda (VirusDisease, 2025)
Angel’s trumpets ( Brugmansia spp.) are important medicinal and ornamental plants belonging to the Solanaceae family, domesticated in the Andean region of South America. Indigenous communities in the Colombian Andes have created unique medicinal cultivars exhibiting a variety of unusual shapes in leaves, and specific uses for ritual or medicinal procedures. These cultivars exhibit leaf symptoms typically associated with viral infections, including mosaic, vein chlorosis, and morphological deformities. Colombian datura virus (CDV) is one of the most studied viruses in Brugmansia , which is distributed globally and affects even other agriculturally significant hosts. The present study aimed to evaluate the viral infections in Colombian cultivars of the Brugmansia genus and the relationship between the presence of viruses and the symptom expression in their leaves. We searched for CDV in the transcriptomes from a set of Solanaceae species and found it mainly in Brugmansia medicinal cultivars and wild solanaceous species. Plant material from B. × candida with different symptoms was collected and inoculated into plants of representative genera in the Solanaceae family, to evaluate symptom expression. We confirmed the sap of CDV-infected Brugmansia ability to cause infections through mechanical inoculation and the CDV presence in the inoculated plants by RT-PCR and Sanger sequencing. Symptoms expressed by these plants included severe leaf deformations in agriculturally important plants such as Physalis peruviana , Solanum lycopersicum , and for the first time, reported the symptoms of the infection in S. melongena and S. quitoense .

Fatty acid profile of Gammarus locusta newly hatched offspring from the wild and from adults farmed on mono-specific macroalgal diets - João P. Sousa; Luísa Marques; Daniela P. Rodrigues; Felisa Rey; Manuel Albuquerque; Maria Rosário M. Domingues; Rafael C. Duarte; Ricardo Calado (Frontiers in Marine Science, 2025)
The accelerated growth of marine aquaculture targeting species that require formulated aquafeeds creates a pressing need to find new sustainable ingredients and additives that can secure a premium farming performance, as well as the nutritional value of farmed species. Marine gammarid amphipods can be an excellent source of essential fatty acids (FA), namely, long-chain n -3 polyunsaturated FA (LC-PUFA). However, their potential contribution to aquaculture feeds remains largely unexplored. The present work evaluated the effect of five mono-specific macroalgal diets ( Ulva sp., Fucus sp., Laminaria sp., Gracilaria sp., and Chondrus sp.) on the FA composition of the offspring of Gammarus locusta fed on these macroalgae and compared it with the offspring of wild conspecifics. Results revealed that offspring from wild G. locusta showed the highest amount of PUFA (4.95 ± 0.31 μg mg -1 DW), as well as essential FA, namely eicosapentaenoic acid (EPA, 20:5 n -3) (2.49 ± 0.21 μg mg -1 DW) and docosahexaenoic acid (DHA, 22:6 n -3) (0.87 ± 0.16 μg mg -1 DW). The treatment with the highest amount of PUFA and EPA was the one using Fucus sp. as a mono-specific macroalgal diet (4.46 ± 0.31 μg mg -1 DW and 2.42 ± 0.24 μg mg -1 DW, respectively). The best levels of DHA in offspring were recorded for specimens feeding on Chondrus sp. (0.56 ± 0.10 μg mg -1 DW). Significant differences in the abundance of stearic acid (18:0) and DHA were observed between the offspring of adults fed algal-based diets and those from the wild. These findings suggest that G. locusta selectively conserves and directly or indirectly biosynthesises essential FA for growth and reproduction, particularly LC-PUFA. Overall, G. locusta can perform a trophic upgrade of its diet, making this gammarid amphipod a promising additive for the formulation of high-quality aquafeeds supplying LC-PUFA.

Cleaning validation in pharmaceutical quality control laboratories: a structured protocol for contamination risk mitigation - Maria J. Moura; André D. Pereira; Daniel J. F. Santos; Ana G. Silva; Carla C. A. D. Paiva; Belmiro P. M. Duarte (DARU Journal of Pharmaceutical Sciences, 2025)
Background Cleaning activities are critical in pharmaceutical manufacturing to prevent cross-contamination of Active Pharmaceutical Ingredients (APIs). Traditionally, cleaning validation protocols have focused on production lines. However, there is a growing trend toward extending these protocols to Quality Control (QC) laboratories, encompassing both glassware and stainless-steel equipment. Objectives This paper presents a systematic approach for developing cleaning validation protocols specifically designed for QC laboratory equipment, aimed at improving cleaning effectiveness and ensuring regulatory compliance. Methods The proposed methodology includes: (i) identifying the worst-case API; (ii) performing recovery studies to optimize sampling methods and solvent selection; and (iii) employing statistical tools such as descriptive analysis and hypothesis testing to refine the protocol in line with current industry standards. Results A case study involving Oxcarbazepine demonstrates the application of the proposed protocol, evaluating surface contamination across various QC instruments and assessing detergent residues to validate cleaning effectiveness. Conclusion The proposed strategy provides a structured, statistically grounded framework for developing cleaning validation protocols in QC laboratories, promoting effective contamination control and adherence to regulatory standards. Graphical abstract

Redefining innovation: the role of co-creation in collaborative new food product strategies - Bruna B Durço; Camile OL Farias; Tatiana C Pimentel; Elson R Tavares Filho; Adriana Gámbaro; Adriano G Cruz; Maria C KH Duarte; Erick A Esmerino (Current Opinion in Food Science, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Sustainability assessment of collagen extraction from fish skins: A comparative life cycle assessment of conventional and NADES-enhanced processes - Miguel P. Batista; Joana Ortigueira; Naiara Fernández; Frédéric B. Gaspar; Maria do Rosário Bronze; Ana Rita C. Duarte; Tiago F. Lopes (Journal of Environmental Chemical Engineering, 2025)

The virome of bubaline (Bubalus bubalis) tonsils reveals an unreported bubaline polyomavirus - Francine C. B. Timm; Fabrício Souza Campos; Luis Janssen; Raíssa Nunes dos Santos; Bruna Paredes-Galarza; Nicole Vieira Stone; Martha Trindade Oliveira; Raíssa Gasparetto; Nicolas Felipe Drum Müller; Alanis da Silva Melgarejo; Miguel Leonetti Corrêa; Lina Marcela Violet Lozano; et al. (Brazilian Journal of Microbiology, 2024)

Production of Oligosaccharides from Pine Nut Shells by Autohydrolysis - Ivone Torrado; Ana Dionísio; Maria C. Fernandes; Luísa Bivar Roseiro; Florbela Carvalheiro; Helena Pereira; Luís C. Duarte (BioEnergy Research, 2023)
Pinus pinea nuts are commercial relevant Mediterranean edible forest nuts, with an increasing production and market value, whose industrial processing yields a lignocellulosic by-product, the pine nut shells, currently only used for combustion. Little research has been done on pine nut shells that could support a value-added application for this residue. This work studies for the first time the production of oligosaccharides by autohydrosis, and aims at an integrated upgrade within the biorefinery framework. Autohydrolysis was explored in the temperature range between 150 and 230 °C (corresponding to severity factors 2.13–4.63). Oligosaccharides, mainly xylo-oligosaccharides (95% of the total), were the key soluble products, reaching 28.7 g/100 g of xylan of the feedstock at the optimal conditions (log R 0 4.01). Other products were monosaccharides and phenolic compounds that reached 7.8 and 4.7 g/L, respectively, under the most severe conditions. The stability of the oligosaccharides at different temperatures (room, 37 °C and 100 °C) and pH (between 1 and 11) grant them significant market potential in the food and pharma sectors. The pre-treated pine nut shells by autohydrolysis presented an improved, although low, enzymatic digestibility (14%), and an improved high-heating value, therefore advising their further valorization by thermochemical pathways.

A common variant close to the “tripwire” linker region of NLRP1 contributes to severe COVID-19 - Vinicius N. C. Leal; Leandro M. Paulino; Raylane A. G. Cambui; Thiago G. Zupelli; Suemy M. Yamada; Leonardo A. T. Oliveira; Valéria de F. Dutra; Carolina B. Bub; Araci M. Sakashita; Ana Paula H. Yokoyama; José M. Kutner; Camila A. Vieira; et al. (Inflammation Research, 2023)

Soil parent material spatial modeling at high resolution from proximal sensing and machine learning: A pilot study - Luiza Maria Pereira Pierangeli; Sérgio Henrique Godinho Silva; Anita Fernanda dos Santos Teixeira; Marcelo Mancini; Renata Andrade; Michele Duarte de Menezes; Mona-Liza C. Sirbescu; João José Marques; David C. Weindorf; Nilton Curi (Journal of South American Earth Sciences, 2023)

Real-time monitoring of the starch cross-linking with citric acid by chemorheological analysis - Gustavo A. Duarte; Maria C. Bezerra; Sílvia H.P. Bettini; Alessandra A. Lucas (Carbohydrate Polymers, 2023)

Soil management effects of extensive pastures, intensive pastures and sugarcane crops on the availability of metals and nutrients in freshwater: A realistic mesocosm approach - Isabele Baima Ferreira Freitas; Paulo José Duarte Neto; Laís Fernanda de Palma Lopes; Maria Paula C. Yoshii; Lais Girotto; Gabriele Verônica de Mello Gabriel; Lais Roberta Sorigotto; Janaina Braga do Carmo; Cassiana Carolina Montagner; Luis Cesar Schiesari; Luiz Antônio Martinelli; Evaldo L.G. Espíndola (Agriculture, Ecosystems & Environment, 2023)

Lifelong exercise training promotes the remodelling of the immune system and prostate signalome in a rat model of prostate carcinogenesis - Elisabete Nascimento-Gonçalves; Fernanda Seixas; Carlos Palmeira; Gabriela Martins; Carolina Fonseca; José Alberto Duarte; Ana I. Faustino-Rocha; Bruno Colaço; Maria João Pires; Maria João Neuparth; Daniel Moreira-Gonçalves; Margarida Fardilha; et al. (GeroScience, 2023)
This work aimed to understand how lifelong exercise training promotes the remodelling of the immune system and prostate signalome in a rat model of PCa. Fifty-five male Wistar rats were divided into four groups: control sedentary, control exercised, induced PCa sedentary and induced PCa exercised. Exercised animals were trained in a treadmill for 53 weeks. Pca induction consisted on the sequential administration of flutamide, N-methyl-N-nitrosourea and testosterone propionate implants. Serum concentrations of C-reactive protein (CRP) and tumor necrosis factor (TNF)-like weak inducer of apoptosis (TWEAK) were not different among groups. Peripheral levels of γδ T cells were higher in Pca exercised group than in the PCa sedentary group ( p < 0.05). Exercise training also induced Oestrogen Receptor (ESR1) upregulation and Mitogen-activated Protein Kinase 13 (MAPK13) downregulation, changed the content of the phosphorylated (at Ser-104) form of this receptor (coded by the gene ESR1) and seemed to increase Erα phosphorylation and activity in exercised PCa rats when compared with sedentary PCa rats. Our data highlight the exercise-induced remodelling of peripheral lymphocyte subpopulations and lymphocyte infiltration in prostate tissue. Moreover, exercise training promotes the remodelling prostate signalome in this rat model of prostate carcinogenesis.

Norfloxacin prophylaxis effect on multidrug resistance in patients with cirrhosis and bacterial infections - Sebastián Marciano; Maria N. Gutierrez-Acevedo; Sabrina Barbero; Lorena del C. Notari; Marina Agozino; Jose L. Fernandez; Maria M. Anders; Nadia Grigera; Florencia Antinucci; Orlando F. Orozco Ganem; Maria D. Murga; Daniela Perez; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Saponite-inspired Materials as Remediation Technologies for Water Treatment: an Overview - Dihêgo Henrique L. Damacena; Pollyana Trigueiro; Victor Hugo Monteiro; Luzia Maria C. Honorio; Thiago Marinho Duarte; Robson Cunha; Marcelo B. Furtini; Maria Gardennia Fonseca; Edson C da Silva-Filho; Josy A. Osajima (Environmental Processes, 2023)

Quantification of SARS-CoV-2 in wastewater samples from hospitals treating COVID-19 patients during the first wave of the pandemic in Brazil - Juliana Calábria de Araújo; Camila L. Madeira; Thiago Bressani; Cíntia Leal; Deborah Leroy; Elayne C. Machado; Luyara A. Fernandes; Maria Fernanda Espinosa; Gabriel Tadeu O. Freitas; Thiago Leão; Vera Tainá Mota; Alyne Duarte Pereira; et al. (Science of The Total Environment, 2023)

Removing chemical and biological pollutants from swine wastewater through constructed wetlands aiming reclaimed water reuse - Maria L. Bôto; Sofia M. Dias; Rute Duarte Crespo; Ana P. Mucha; C. Marisa R. Almeida (Journal of Environmental Management, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Different faces of cigarette butts, the most abundant beach litter worldwide - Maria Christina B. Araújo; Monica F. Costa; Jacqueline S. Silva-Cavalcanti; Armando C. Duarte; Vanessa Reis; Teresa A. Rocha-Santos; João Pinto da Costa; Violeta Girão (Environmental Science and Pollution Research, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Global proteomic analysis of the follicular fluid from brown brocket deer (Mazama gouazoubira; Fisher, 1814) - Thais T. S. Souza; Maurício F. van Tilburg; Maria J. B. Bezerra; Luciana D. Rola; Leda M. C. Pereira; José M. B. Duarte; Maiana S. Chaves; Luciana M. Melo; Arlindo A. A. N. Moura; Vicente J. F. Freitas (European Journal of Wildlife Research, 2022)

Elusive deer occurrences at the Atlantic Forest: 20 years of surveys - Márcio Leite de Oliveira; Francisco Grotta-Netto; Pedro Henrique de Faria Peres; Alexandre Vogliotti; Carlos Rodrigo Brocardo; Jorge José Cherem; Mariana Landis; Roberta Montanheiro Paolino; Roberto Fusco-Costa; Andressa Gatti; Danielle Oliveira Moreira; Paula Modenesi Ferreira; et al. (Mammal Research, 2022)

Acarbose presents in vitro and in vivo antileishmanial activity against Leishmania infantum and is a promising therapeutic candidate against visceral leishmaniasis - Rafaella R. Costa; João A. Oliveira-da-Silva; Thiago A. R. Reis; Grasiele S. V. Tavares; Débora V. C. Mendonça; Camila S. Freitas; Daniela P. Lage; Vívian T. Martins; Luciana M. R. Antinarelli; Amanda S. Machado; Raquel S. Bandeira; Fernanda Ludolf; et al. (Medical Microbiology and Immunology, 2021)

Susan Lynn Williams: the Life of an Exceptional Scholar, Leader, and Friend (1951–2018) - William C. Dennison; Matthew E. S. Bracken; Maria Brown; John F. Bruno; James T. Carlton; Robert C. Carpenter; Tim J. B. Carruthers; Megan N. Dethier; Carlos M. Duarte; Thomas R. Fisher; James W. Fourqurean; Richard K. Grosberg; et al. (Estuaries and Coasts, 2021)
Susan Lynn Williams (1951–2018) was an exceptional marine ecologist whose research focused broadly on the ecology of benthic nearshore environments dominated by seagrasses, seaweeds, and coral reefs. She took an empirical approach founded in techniques of physiological ecology. Susan was committed to applying her research results to ocean management through outreach to decision-makers and resource managers. Susan’s career included research throughout the USA in tropical, temperate, and polar regions, but she specialized in tropical marine ecology. Susan’s scholarship, leadership, and friendship touched many people, leading to this multi-authored paper. Susan’s scholarship was multi-faceted, and she excelled in scientific discovery, integration of scientific results, application of science for conservation, and teaching, especially as a mentor to undergraduate and graduate students and postdoctoral scholars. Susan served in a variety of leadership positions throughout her career. She embodied all facets of leadership; leading by example, listening to others, committing to the “long haul,” maintaining trust, and creating a platform for all to shine. Susan was an important role model for women in science. Susan was also a loyal friend, maintaining friendships for many decades. Susan loved cooking and entertaining with friends. This paper provides an overview of the accomplishments of Susan in the broad categories of scholarship, leadership, and friendship.

Diversity of tomato-infecting begomoviruses and spatiotemporal dynamics of an endemic viral species of the Brazilian Atlantic rain forest biome - Macária F. Duarte; Maria E. N. Fonseca; Hélcio Costa; Niday A. N. Fernandes; Ailton Reis; Leonardo S. Boiteux; Rita C. Pereira-Carvalho (Virus Genes, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Phytochemical Characterization, Bioactivities Evaluation and Synergistic Effect of Arbutus unedo and Crataegus monogyna Extracts with Amphotericin B - Alexandra T. Coimbra; Ângelo F. S. Luís; Maria T. Batista; Susana M. P. Ferreira; Ana Paula C. Duarte (Current Microbiology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Influence of DRD1 and DRD3 Polymorphisms in the Occurrence of Motor Effects in Patients with Sporadic Parkinson’s Disease - Erinaldo Ubirajara Damasceno dos Santos; Elaine Bandeira Cavalcanti Duarte; Laura Maria Ramos Miranda; Andore Guescel C. Asano; Nadja Maria Jorge Asano; Maria de Mascena Diniz Maia; Paulo Roberto Eleutério de Souza (NeuroMolecular Medicine, 2019)

Involvement of the Cholinergic Parameters and Glial Cells in Learning Delay Induced by Glutaric Acid: Protection by N-Acetylcysteine - Fernanda Silva Rodrigues; Viviane Nogueira de Zorzi; Marla Parizzi Funghetto; Fernanda Haupental; Alexandra Seide Cardoso; Sara Marchesan; Andréia M. Cardoso; Maria Rosa C. Schinger; Alencar Kolinski Machado; Ivana Beatrice Mânica da Cruz; Marta Maria Medeiros Frescura Duarte; Léder L. Xavier; et al. (Molecular Neurobiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Distillery Residues from Cistus ladanifer (Rockrose) as Feedstock for the Production of Added-Value Phenolic Compounds and Hemicellulosic Oligosaccharides - Júnia Alves-Ferreira; Luís C. Duarte; Ana Lourenço; Luísa B. Roseiro; Maria C. Fernandes; Helena Pereira; Florbela Carvalheiro (BioEnergy Research, 2019)

Better estimates of soil carbon from geographical data: a revised global approach - Sandra Duarte-Guardia; Pablo L. Peri; Wulf Amelung; Douglas Sheil; Shawn W. Laffan; Nils Borchard; Michael I. Bird; Wouter Dieleman; David A. Pepper; Brian Zutta; Esteban Jobbagy; Lucas C. R. Silva; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

Spatiotemporal trends of area burnt in the Iberian Peninsula, 1975–2013 - João M. N. Silva; Maria Vanesa Moreno; Yannick Le Page; Duarte Oom; Ioannis Bistinas; José Miguel C. Pereira (Regional Environmental Change, 2019)

A first glance into the nutritional properties of the sea cucumber Parastichopus regalis from the Mediterranean Sea (SE Spain) - Christina C Roggatz; Mercedes González-Wangüemert; Hugo Pereira; Catarina Vizetto-Duarte; Maria João Rodrigues; Luísa Barreira; Manuela Moreira da Silva; João Varela; Luísa Custódio (Natural Product Research, 2018)

Communities of arbuscular mycorrhizal fungi under Picconia azorica in native forests of Azores - Catarina Drumonde Melo; Sara Luna; Claudia Krüger; Christopher Walker; Duarte Mendonça; Henrique M. A. C. Fonseca; Maria Jaizme-Vega; Artur Câmara Machado (Symbiosis, 2018)

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Topography‐driven isolation, speciation and a global increase of endemism with elevation - Manuel J. Steinbauer; Richard Field; John‐Arvid Grytnes; Panayiotis Trigas; Claudine Ah‐Peng; Fabio Attorre; H. John B. Birks; Paulo A. V. Borges; Pedro Cardoso; Chang‐Hung Chou; Michele De Sanctis; Miguel M. de Sequeira; et al. (Global Ecology and Biogeography, 2016)
Aim Higher‐elevation areas on islands and continental mountains tend to be separated by longer distances, predicting higher endemism at higher elevations; our study is the first to test the generality of the predicted pattern. We also compare it empirically with contrasting expectations from hypotheses invoking higher speciation with area, temperature and species richness. Location Thirty‐two insular and 18 continental elevational gradients from around the world. Methods We compiled entire floras with elevation‐specific occurrence information, and calculated the proportion of native species that are endemic (‘percent endemism’) in 100‐m bands, for each of the 50 elevational gradients. Using generalized linear models, we tested the relationships between percent endemism and elevation, isolation, temperature, area and species richness. Results Percent endemism consistently increased monotonically with elevation, globally. This was independent of richness–elevation relationships, which had varying shapes but decreased with elevation at high elevations. The endemism–elevation relationships were consistent with isolation‐related predictions, but inconsistent with hypotheses related to area, richness and temperature. Main conclusions Higher per‐species speciation rates caused by increasing isolation with elevation are the most plausible and parsimonious explanation for the globally consistent pattern of higher endemism at higher elevations that we identify. We suggest that topography‐driven isolation increases speciation rates in mountainous areas, across all elevations and increasingly towards the equator. If so, it represents a mechanism that may contribute to generating latitudinal diversity gradients in a way that is consistent with both present‐day and palaeontological evidence.

Cytokines profile and its correlation with endothelial damage and oxidative stress in patients with type 1 diabetes mellitus and nephropathy - Rodrigo M. C. Pestana; Caroline P. Domingueti; Rita C. F. Duarte; Rodrigo B. Fóscolo; Janice S. Reis; Ana Maria S. Rodrigues; Laís B. Martins; Lirlândia P. Sousa; Daniela P. Lage; Cláudia N. Ferreira; Adaliene V. M. Ferreira; Ana P. Fernandes; et al. (Immunologic Research, 2016)

Lethal neonatal meningoencephalitis caused by multi-drug resistant, highly virulent Escherichia coli - Junaid Iqbal; Kevin R. Dufendach; John C. Wellons; Maria G. Kuba; Hilary H. Nickols; Oscar G. Gómez-Duarte; James L. Wynn (Infectious Diseases, 2016)

Extreme pH Conditions at a Natural CO2 Vent System (Italy) Affect Growth, and Survival of Juvenile Pen Shells (Pinna nobilis) - Lorena Basso; Iris E. Hendriks; Alejandro B. Rodríguez-Navarro; Maria C. Gambi; Carlos M. Duarte (Estuaries and Coasts, 2015)

BbrizAGL6 Is Differentially Expressed During Embryo Sac Formation of Apomictic and Sexual Brachiaria brizantha Plants - Larissa Arrais Guimarães; Diva Maria de A. Dusi; Simona Masiero; Francesca Resentini; Ana Cristina M. M. Gomes; Érica Duarte Silveira; Lilian Hasegawa Florentino; Júlio Carlyle M. Rodrigues; Lucia Colombo; Vera Tavares de C. Carneiro (Plant Molecular Biology Reporter, 2013)

Decomposition and nutrient release in leaves of Atlantic Rainforest tree species used in agroforestry systems - Edivânia M. G. Duarte; Irene M. Cardoso; Thomas Stijnen; Maria Alice F. C. Mendonça; Marino S. Coelho; Reinaldo B. Cantarutti; Thomas W. Kuyper; Ecila M. A. Villani; Eduardo S. Mendonça (Agroforestry Systems, 2013)

Hematological indices and activity of NTPDase and cholinesterase enzymes in rats exposed to cadmium and treated with N-acetylcysteine - Jamile F. Gonçalves; Marta M. M. F. Duarte; Amanda M. Fiorenza; Roselia M. Spanevello; Cinthia M. Mazzanti; Roberta Schmatz; Margarete D. Bagatini; Fabiane G. Antes; Pauline Costa; Fátima H. Abdalla; Valderi L. Dressler; Vera M. Morsch; et al. (BioMetals, 2012)

Steady-state level of epidermal growth factor (EGF) mRNA and effect of EGF on in vitro culture of caprine preantral follicles - Juliana Jales H. Celestino; Jamily B. Bruno; Márcia Viviane A. Saraiva; Rebeca M. P. Rocha; Ivina R. Brito; Ana Beatriz G. Duarte; Valdevane R. Araújo; Cleidson M. G. Silva; Maria Helena T. Matos; Claudio C. Campello; José Roberto V. Silva; José Ricardo Figueiredo (Cell and Tissue Research, 2011)

The small nuclear ribonucleoprotein U1A interacts with NS5 from yellow fever virus - Roberta V. M. Bronzoni; Maria C. F. S. Madrid; Danilo V. B. Duarte; Vanessa O. A. Pellegrini; Carolina C. Pacca; Ana C. V. Carmo; Cleslei F. Zanelli; Sandro R. Valentini; Carolina Santacruz-Pérez; João A. R. G. Barbosa; Carol S. Lutz; Paula Rahal; et al. (Archives of Virology, 2011)

Genetic diversity of three endangered species of Echium L. (Boraginaceae) endemic to Cape Verde Islands - Maria M. Romeiras; Helena C. Cotrim; Maria C. Duarte; Maria S. Pais (Biodiversity and Conservation, 2007)

Efficient Genetic Transformation System for the Ochratoxigenic Fungus Aspergillus carbonarius - Luiz Rodrigo I. Morioka; Márcia C. Furlaneto; Andréa C. Bogas; Patrícia Pompermayer; Rubens T. D. Duarte; Maria Lúcia C. Vieira; Maria Angélica Ehara Watanabe; Maria Helena P. Fungaro (Current Microbiology, 2006)

Effect of a high-altitude expedition to a Himalayan peak (Pumori, 7,161m) on plasma and erythrocyte antioxidant profile - Jos Magalhes; Antnio Ascenso; Franklim Marques; Jos M. C. Soares; Rita Ferreira; Maria J. Neuparth; Jos A. Duarte (European Journal of Applied Physiology, 2005)

Acute and severe hypobaric hypoxia-induced muscle oxidative stress in mice: the role of glutathione against oxidative damage - Jos Magalhes; Jos M. C. Soares; Maria J. Neuparth; Rita Ferreira; Jos Oliveira; Francisco Amado; Jos A. Duarte; Antnio Ascenso (European Journal of Applied Physiology, 2004)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)